Evaluation of IFA, MAT, ELISAs and immunoblotting for the detection of anti-Toxoplasma gondii antibodies in paired serum and aqueous humour samples from experimentally infected pigs - Garcia, João Luis; Gennari, Solange Maria; Navarro, Italmar Teodorico; Machado, Rosângela Zacarias [UNESP]; Headley, Selwyn Arligton; Vidotto, Odilon; da Silva Guimarães Jr., José; Bugni, Felipe Monteiro; Igarashi, Michelle (Elsevier, 2008)
The study evaluated the efficiency of diagnostic laboratory methods to detect anti-Toxoplasma gondii antibodies in paired serum and aqueous humour samples from experimentally infected pigs. 18-mixed breed pigs were used during the experiment; these were divided into two groups, G1 (infected group, n = 10) and G2 (uninfected group, n = 8). Infection was performed with 4 × 10 4 VEG strain oocysts at day 0 by the oral route in G1 animals. All pigs were euthanized at day 60, when retina, aqueous humour, and blood samples were collected. Anti-T. gondii antibody levels were assessed in serum (s) and aqueous humour (ah) by indirect immunofluorescence assay (IFA), modified agglutination test (MAT), m-ELISA (using crude membranes from T. gondii tachyzoites as antigen) and r-ELISA (using rhoptries from T. gondii tachyzoites as antigen). Polymerase chain reactions (PCR) of samples from the retina were performed by using Tox4 and Tox5 primers. Antibody titers of G1 animals ranged from 128 to 1024 and from 16 to 256 in serum and aqueous humour, respectively. There were differences in the correlation coefficients between IFA(s) × IFA (ah) (r = 0.62, P = 0.05), MAT(s) × MAT (ah) (r = 0.97, P < 0.0001); however, there was no significant difference between r-ELISA(s) × r-ELISA (ah) (r = 0.14, P = 0.7). Antibodies present in serum and aqueous humour recognized similar antigens. Samples of retina were positive by PCR in 30% (3/10) of infected pigs. G2 animals remained without antibody levels and were PCR negative throughout the experiment. These results suggest that the use of a combination of tests and immunoblotting for paired aqueous humour and serum samples could improve the sensitivity and specificity for the diagnosis of ocular toxoplasmosis. © 2007 Elsevier Ltd. All rights reserved.
Keywords: Aqueous humour; ELISA; IFAT; MAT; PCR; Pigs; Toxoplasma gondii; protozoon antibody; agglutination test; animal euthanasia; animal experiment; animal model; animal tissue; antibody blood level; antibody detection; antibody titer; aqueous humor; controlled study; correlation coefficient; diagnostic value; enzyme linked immunosorbent assay; immunoblotting; immunofluorescence test; intermethod comparison; nonhuman; polymerase chain reaction; retina; sensitivity and specificity; statistical significance; swine; tachyzoite; toxoplasmosis; Agglutination Tests; Animals; Antibodies, Protozoan; Aqueous Humor; Enzyme-Linked Immunosorbent Assay; Fluorescent Antibody Technique, Indirect; Immunoblotting; Immunoglobulin G; Swine; Swine Diseases; Toxoplasmosis, Animal; Animalia; Suidae